Relationship of Age, Body Mass Index, Gravida, and Parity in Pregnant Women with the Incidence Preeclampsia - Muhammad Alamsyah Aziz; Aditya Wibowo; Nadia Larastri Almira; Tjut Sutjighassani (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2022)
AbstractObjective: According to the 2016 Routine Health Profile Report, the exact causes of maternal mortality are hypertension (33.07%) and bleeding (27%). The exact cause of preeclampsia is unknown and is therefore referred to as the “disease of theory”. This study aimed to determine the relationship between age, BMI, gravida and parity with preeclampsia.Methods: This cross-sectional, analytic observational study, conducted in Hasan Sadikin Hospital, Bandung. Subjects are pregnant women undergoing antenatal care at Hasan Sadikin Hospital Bandung, in May 2020 a total of 40 women with a gestational age of ≥ 20 weeks. The univariate and bivariate data were analyzed with SPSS. The Saphiro Wilk test was used to measure the data normality. The ANOVA one-way test and Fisher test were used to analyze the bivariate data.Results: Results show that of 19 samples with preeclampsia, 13 people (68.4%) were older than 35 years old with p-value of 0.042 which indicates a significant relationship. There is no significant difference between BMI, gravida, and parity, with the incidence of preeclampsia with p-value 0.602, 0.664, and 0.661 respectively.Conclusion: There is a relationship between mother’s age and the incidence of preeclampsia in Dr. Hasan Sadikin Hospital with p value = 0.042. This means older than 35 years old mothers have a tendency to develop preeclampsia.Hubungan Usia, Indeks Massa Tubuh, Gravida, dan Paritas pada Ibu Hamil dengan Insidensi PreeklamsiaAbstrakTujuan: Penelitian ini bertujuan untuk mengetahui hubungan paritas dengan preeklamsia.Metode: Studi observasional analitik potong lintang ini dilakukan di Rumah Sakit Hasan Sadikin Bandung. Subjek adalah ibu hamil yang menjalani pemeriksaan kehamilan di RS Hasan Sadikin Bandung, pada bulan Mei 2020 sejumlah 40 orang dengan usia kehamilan ≥ 20 minggu. Data univariat dan bivariat dianalisis dengan SPSS. Uji Saphiro Wilk digunakan untuk mengukur normalitas data. Uji satu arah ANOVA dan uji Fisher digunakan untuk menganalisis data bivariat.Hasil: Hasil penelitian menunjukkan bahwa dari 19 sampel dengan preeklamsia, 13 orang (68,4%) berusia lebih dari 35 tahun dengan p-value 0,042 yang menunjukkan hubungan yang signifikan.Kesimpulan: Ada hubungan usia ibu dengan kejadian preeklampsia di RSUD Dr. Hasan Sadikin dengan nilai p = 0,042. Ini berarti ibu yang berusia lebih dari 35 tahun memiliki kecenderungan untuk mengalami preeklamsia.Kata kunci: Preeklamsia, usia, IMT, gravida, paritas